The Relationship between English Language Fluency and Learning Engagement : A Case Study among First-Year Undergraduates - Nur Rasyidah, Othman; Chuah, Kee Man (Human Resource Management Academic Research Society, 2021)
The notion that learners with lower English language fluency tend to be less engaged in university classes still lacks further investigation. Evidence from previous studies was not conclusive and seems to suggest students with lower proficiency in the language are at risk of dropping out. This study aimed to explore the relationship between English fluency and learning engagement among first-year undergraduate students in a Malaysian university. A total of 144 students from 10 faculties participated in the study. Data were collected through a self-reported questionnaire about their English fluency, Malaysian University English Test (MUET) band and their level of engagement in the classroom. Statistical analyses revealed significant correlations in language fluency and learning engagement in which students with higher fluency were more engaged in the classroom. This study also showed students who reported higher level of perceived English language fluency and learning engagement obtained higher grades. In addition, regression analysis revealed that listening and writing skills significantly contributed to the model, which implies fluency in these two skills are more important in university settings.